2019
DOI: 10.1002/ijc.32298
|View full text |Cite|
|
Sign up to set email alerts
|

Education and gastric cancer risk—An individual participant data meta‐analysis in the StoP project consortium

Abstract: Low socioeconomic position (SEP) is a strong risk factor for incidence and premature mortality from several cancers. Our study aimed at quantifying the association between SEP and gastric cancer (GC) risk through an individual participant data meta‐analysis within the “Stomach cancer Pooling (StoP) Project”. Educational level and household income were used as proxies for the SEP. We estimated pooled odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) across levels of education and household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 47 publications
2
29
3
1
Order By: Relevance
“…We observed a higher risk reduction among individuals in the low socioeconomic group for the consumption of fruits and noncitrus fruits, though, differences were not statistically significant, while in the StoP Project's citrus fruits study, the interaction was statistically significant 10 . This suggests that not only citrus fruits but all fruits and vegetables might counterbalance the negative effects of the lifestyle risk factors associated with low socioeconomic status 57 . Regional differences were also observed, reflecting not only the different diets but also the detail of the FFQs applied regarding the number and types of food items included.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We observed a higher risk reduction among individuals in the low socioeconomic group for the consumption of fruits and noncitrus fruits, though, differences were not statistically significant, while in the StoP Project's citrus fruits study, the interaction was statistically significant 10 . This suggests that not only citrus fruits but all fruits and vegetables might counterbalance the negative effects of the lifestyle risk factors associated with low socioeconomic status 57 . Regional differences were also observed, reflecting not only the different diets but also the detail of the FFQs applied regarding the number and types of food items included.…”
Section: Discussioncontrasting
confidence: 57%
“…10 This suggests that not only citrus fruits but all fruits and vegetables might counterbalance the negative effects of the lifestyle risk factors associated with low socioeconomic status. 57 Regional F I G U R E 2 Dose-response relationship between A, fruits; B, noncitrus fruits; and C, vegetables and gastric cancer, fitted by a fractional polynomial. 95% CI, 95% confidence interval; OR, odds ratio differences were also observed, reflecting not only the different diets but also the detail of the FFQs applied regarding the number and types of food items included.…”
Section: Resultsmentioning
confidence: 99%
“…56 When stomach cardia and non-cardia are analysed separately, conflicting conclusions are seen: sometimes associations of similar magnitudes are found for both subsites 46 ; are somewhat stronger for non-cardia 47 ; or somewhat stronger for cardia. 49,57 The two latter studies were large multi-centric case-control studies that also stratified by histological subtype and found more pronounced educational effects for intestinal compared to diffuse type of gastric adenocarcinoma. Furthermore, they investigated to what extent major risk factors explain SES inequality and both found that surprisingly little of the inequality could be attributed to lifestyle factors such as smoking, alcohol, diet, BMI and physical inactivity, or Helicobacter pylori infection.…”
Section: Cancers Of the Upper Aerodigestive Tract And Stomach Cancermentioning
confidence: 99%
“…Cigarette smoking and heavy alcohol consumption are other well-known risk factors for GC, with a 40% excess risk in smokers versus non-smokers [13] and a 50% increased risk for heavy drinkers compared to never drinkers [14]. As for many other cancers, low socioeconomic status has also been identified as a risk factor for GC; in the latest StoP analysis, the pooled OR for the highest compared to the lowest level of education was 0.60 (95% CI, 0.44-0.84) [15]. With reference to dietary factors, data from the StoP project confirmed that meat consumption is a risk factor [16], whereas fruit intake is protective [17].…”
Section: Environmental Factors and Gcmentioning
confidence: 99%